2001
DOI: 10.1016/s0004-9514(14)60274-9
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of five methods for assessing shoulder range of motion

Abstract: In symptomatic subjects, the reliability of tests for shoulder joint range of motion has yet to be determined. For this reason, inter-rater and intra-rater agreement trials were undertaken to ascertain the reliability of visual estimation, goniometry, still photography, "stand and reach" and hand behind back reach for six different shoulder movements. Intra-class correlation coefficients (Rho) were derived by using a random effects model. For flexion, abduction and external rotation fair to good reliability wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
182
1
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(206 citation statements)
references
References 12 publications
9
182
1
9
Order By: Relevance
“…However, Senbursa et al (2007) reported that a group following a manual therapy with exercise program and an exercise only program resulted in decreases in pain and improvement of function 1) , but as statistically significant improvements were found only in the manual therapy with exercise program group, as was noted in the present study. These results suggest that strengthening exercise with intervention aiming to achieve proper motion is more useful for increasing joint mobility, decreasing pain and improving the functional ability than strengthening exercise alone 1,23) . Isokinetic equipment can accurately measure the muscle strength that occurs at constant angular velocity and a range of motion, and the peak torque is a very important index for estimating the maximum motor ability of muscles 27) .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, Senbursa et al (2007) reported that a group following a manual therapy with exercise program and an exercise only program resulted in decreases in pain and improvement of function 1) , but as statistically significant improvements were found only in the manual therapy with exercise program group, as was noted in the present study. These results suggest that strengthening exercise with intervention aiming to achieve proper motion is more useful for increasing joint mobility, decreasing pain and improving the functional ability than strengthening exercise alone 1,23) . Isokinetic equipment can accurately measure the muscle strength that occurs at constant angular velocity and a range of motion, and the peak torque is a very important index for estimating the maximum motor ability of muscles 27) .…”
Section: Discussionmentioning
confidence: 90%
“…A 5-min rest period was provided between each test 22) . The shoulder range of motion was assessed using a goniometer during active shoulder movement without pain 23,24) . The range of motion included flexion, extension, abduction, adduction, external rotation and internal rotation of the shoulder joint.…”
Section: Methodsmentioning
confidence: 99%
“…Good reliability (ICC .76-.91) of goniometry for shoulder AROM has been established in subjects with shoulder pain. 38 The UQYBT was used to determine closed chain performance as described by Gorman et al 39 with high reliability (ICC .90). The test was performed with the participant in the push-up position.…”
Section: Outcome Measures and Proceduresmentioning
confidence: 99%
“…Um outro aspecto importante da aferição goniométrica é a conϐiabilidade da medida intra-avaliador, que representa a habilidade de um único avaliador obter resultados consistentes em mensurações sucessivas, e a inter-avaliador, que representa a concordância entre medidas da mesma articulação por diferentes avaliadores (Rothstein et al 1983, Gajdosik & Bohannon 1987, Norkin & White 1997, Hayes et al 2001, Araújo et al 2009. No presente estudo a mensurações com menor conϐiabilidade foram as do avaliador 2, em especial no carpo e cotovelo, provavelmente por ser o avaliador menos experiente.…”
Section: Discussionunclassified